Hungry translations : relearning the world through radical vulnerability - Nagar, Richa (Transformations: womanist, feminist, and indigenous studies., 2019)
Experts often assume that the poor, hungry, rural, and/or precarious need external interventions. They frequently fail to recognize how the same people create politics and knowledge by living and honing their own dynamic visions. How might scholars and teachers working in the Global North ethically participate in producing knowledge in ways that connect across different meanings of struggle, hunger, hope, and the good life?Informed by over twenty years of experiences in India and the United States, Hungry Translations bridges these divides with a fresh approach to academic theorizing. Through in-depth reflections on her collaborations with activists, theatre artists, writers, and students, Richa Nagar discusses the ongoing work of building embodied alliances among those who occupy different locations in predominant hierarchies. She argues that such alliances can sensitively engage difference through a kind of full-bodied immersion and translation that refuses comfortable closures or transparent renderings of meanings. While the shared and unending labor of politics makes perfect translation--or retelling--impossible, hungry translations strive to make our knowledges more humble, more tentative, and more alive to the creativity of struggle.